2011
DOI: 10.1111/j.1600-0536.2011.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sensitization to preservatives estimated on the basis of patch test data and exposure, according to a sample of 3541 leave-on products

Abstract: High frequencies of sensitization may be put into perspective by the frequent use of certain preservatives. Despite infrequent use, others (with higher potencies or too high use concentrations) may turn out to be associated with an increased risk. Hazard assessment should be supplemented by risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 27 publications
1
43
0
3
Order By: Relevance
“…In the larger collective, the reactions were classified as irritative or questionable in 0.53% of the patients (Schnuch et al 2011;Uter et al 2010). An evaluation of the patch test results from 5183 patients with and 14 722 patients without atopic eczema documented between 1995 and 1999 in the clinics of the IVDK showed that in these collectives there is practically no difference in the incidence of reactions at 0.28% and 0.30%, respectively.…”
Section: Allergenic Effectsmentioning
confidence: 99%
“…In the larger collective, the reactions were classified as irritative or questionable in 0.53% of the patients (Schnuch et al 2011;Uter et al 2010). An evaluation of the patch test results from 5183 patients with and 14 722 patients without atopic eczema documented between 1995 and 1999 in the clinics of the IVDK showed that in these collectives there is practically no difference in the incidence of reactions at 0.28% and 0.30%, respectively.…”
Section: Allergenic Effectsmentioning
confidence: 99%
“…1,2,9,11 Finally, the relatively high incidence detected in studies on patients with eczema performed in skin allergy units highlights the marked allergenicity of these substances. 12,13 Sources MCI/MI and MI are widely used in consumer and in industrial products.…”
Section: Molecular Structure and Sensitization Studiesmentioning
confidence: 99%
“…For some authors, 18 this measure has been effective; for others, 11,17 however, it has not succeeded in sufficiently reducing rates of sensitization to MCI/MI, which have remained at 1.8-4.4% for the last 20 years. 6,11,12,18,19 Furthermore, during the last 4 years there has been an alarming increase in sensitization to MCI/MI (4-5%). 3,18 We confirmed this finding in our department, where the rate increased from 4.49% during the period October 2006-September 2008 6 to 10% in October 2011-September 2013 ( Table 2).…”
Section: Industrial Productsmentioning
confidence: 99%
“…Menschen [31]. [32,37]. Auf Basis klinischer Daten erschien Gentamicin als häufiges Allergen, unter Berücksichti-gung der Exposition weist jedoch Kanamycin ein höheres Kontaktallergierisiko auf.…”
Section: Nickelallergie Bei Jungen Frauenunclassified
“…Auf Basis klinischer Daten erschien Gentamicin als häufiges Allergen, unter Berücksichti-gung der Exposition weist jedoch Kanamycin ein höheres Kontaktallergierisiko auf. Bei den Konservierungsstoffen zeigten Phenoxyethanol, Benzylalkohol und Parabene trotz ihrer weiten Verbreitung ein (sehr) geringes Sensibilisierungsrisiko; dieses war geringer als das mit zum Beispiel Formaldehydabspaltern oder Isothiazolinonen assoziierte [32,37].…”
Section: Nickelallergie Bei Jungen Frauenunclassified